A new method to calculate the maximum dose of local anesthetics - Rocha, Julierme Ferreira; Fan, Song; Dias Ribeiro, Eduardo (ARCHIVES OF HEALTH INVESTIGATION, 2020)
The purpose of this correspondence is to present a suggestion of a simple and practical formula to calculate the maximum recommended dose of local anesthetics. We believe that using the proposed formula, it will be easier to calculate the maximum recommended dose. Descriptors: : Local Anesthetics; Drug Dosage Calculation; Clinical Practice Pattern. References Malamed SF. Handbook of local anesthesia. 6th ed. St Louis: Mosby 2013.